Феномен наукового тексту - Павлов, О. С. (ХНУРЕ, 2019)
The work considered the uniqueness scientific text in professional activities; the author also specifies the meaning of such a concept as «term», «nomenclature». The article also discusses the meaning and construction of various professionalisms, where it came from and what it means